Mechanically induced osteogenic lineage commitment of stem cells - Chen, Julia C (BioMed Central, 2013)
Bones adapt to accommodate the physical forces they experience through changes in architecture and mass. Stem cells differentiate into bone-forming osteoblasts, and mechanical stimulation is involved in this process. Various studies have applied controlled mechanical stimulation to stem cells and investigated the effects on osteogenic lineage commitment. These studies demonstrate that physical stimuli can induce osteogenic lineage commitment. Tension, fluid shear stress, substrate material properties, and cell shape are all factors that influence osteogenic differentiation. In particular, the level of tension is important. Also, rigid substrates with stiffness similar to collagenous bone induce osteogenic differentiation, while softer substrates induce other lineages. Finally, cells allowed to adhere over a larger area are able to differentiate towards the osteogenic lineage while cells adhering to a smaller area are restricted to the adipogenic lineage. Stem cells are able to sense their mechanical environments through various mechanosensors, including the cytoskeleton, focal adhesions, and primary cilia. The cytoskeleton provides a structural frame for the cell, and myosin interacts with actin to generate cytoskeletal tension, which is important for mechanically induced osteogenesis of stem cells. Adapter proteins link the cytoskeleton to integrins, which attach the cell to the substrate, forming a focal adhesion. A variety of signaling proteins are also associated with focal adhesions. Forces are transmitted to the substrate at these sites, and an intact focal adhesion is important for mechanically induced osteogenesis. The primary cilium is a single, immotile, antenna-like structure that extends from the cell into the extracellular space. It has emerged as an important signaling center, acting as a microdomain to facilitate biochemical signaling. Mechanotransduction is the process by which physical stimuli are converted into biochemical responses. When potential mechanosensors are disrupted, the activities of components of mechanotransduction pathways are also inhibited, preventing mechanically induced osteogenesis. Calcium, mitogen-activated protein kinase/extracellular signal-regulated kinase, Wnt, Yes-associated protein/transcriptional coactivator with PDZ-binding motif and RhoA/Rho kinase signaling are some of the mechanotransduction pathways proposed to be important. In this review, types of mechanical stimuli, mechanosensors, and key pathways involved in mechanically induced osteogenesis of stem cells are discussed.